2019
DOI: 10.1016/j.jcol.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopic findings in patients younger than 40 years

Abstract: Objective  To analyze the main endoscopic findings in patients under 40 years of age and the main indications for colonoscopy in these patients. Methods  A retrospective study with 362 reports of patients under 40 years of age who underwent colonoscopy from January 2014 to June 2017 at the colonoscopy service of the General Hospital Roberto Santos. Colon preparation was performed with mannitol and the patients underwent sedation as the anesthetist criteria. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…A small but significant proportion of our young adult population was found to have IBD at 10%, while the prevalence of MC appears to be very low at only 2%. Other studies have reported rates for IBD from 11.9 to 18.5% in similar age groups [3,[9][10][11]. We found no similar studies on the DY for MC in the young.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…A small but significant proportion of our young adult population was found to have IBD at 10%, while the prevalence of MC appears to be very low at only 2%. Other studies have reported rates for IBD from 11.9 to 18.5% in similar age groups [3,[9][10][11]. We found no similar studies on the DY for MC in the young.…”
Section: Discussioncontrasting
confidence: 77%
“…These diseases are of particular interest given their prevalence and increasing incidence in young adults, and the necessity of lower GI endoscopy for diagnosis [5][6][7][8]. While a small number of studies report a significant yield for IBD, data available for MC are lacking [3,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of colonoscopy to detect colorectal neoplasia in symptomatic persons under the age of 50 remains controversial, as benign causes account for the vast majority of symptoms in young populations. 79…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of colonoscopy to detect colorectal neoplasia in symptomatic persons under the age of 50 remains controversial, as benign causes account for the vast majority of symptoms in young populations. [7][8][9] Nevertheless, recent research suggests that there is an upward trend of CRC and advanced colonic polyps in young adults, particularly those between the ages of 40 and 49. 10,11 These findings have led several society guidelines to recommend lowering the age cut-off for screening performance.…”
Section: Introductionmentioning
confidence: 99%